2008
DOI: 10.1037/a0012702
|View full text |Cite
|
Sign up to set email alerts
|

Does stereotype threat affect test performance of minorities and women? A meta-analysis of experimental evidence.

Abstract: A meta-analysis of stereotype threat effects was conducted and an overall mean effect size of |.26| was found, but true moderator effects existed. A series of hierarchical moderator analyses evidenced differential effects of race- versus gender-based stereotypes. Women experienced smaller performance decrements than did minorities when tests were difficult: mean ds = |.36| and |.43|, respectively. For women, subtle threat-activating cues produced the largest effect, followed by blatant and moderately explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
593
4
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(648 citation statements)
references
References 112 publications
26
593
4
19
Order By: Relevance
“…On average, neutral writers taking the MCAT or LSAT scored in the 46th and 23rd percentile, respectively, whereas expressive writers taking these exams scored in the 58th and 43th percentile; a difference of this magnitude is similar to raising one's MCAT score from 25 to 27 and one's LSAT score from 144 to 149. The effect size associated with these test score differences (r ϭ .24) is not dissimilar to those found in some stereotype threat experiments, in which lab-based test performance is assessed after emotions/anxiety levels are manipulated (average rs range from .05 to .37, depending on the subgroup/ specific methodology; Nguyen & Ryan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On average, neutral writers taking the MCAT or LSAT scored in the 46th and 23rd percentile, respectively, whereas expressive writers taking these exams scored in the 58th and 43th percentile; a difference of this magnitude is similar to raising one's MCAT score from 25 to 27 and one's LSAT score from 144 to 149. The effect size associated with these test score differences (r ϭ .24) is not dissimilar to those found in some stereotype threat experiments, in which lab-based test performance is assessed after emotions/anxiety levels are manipulated (average rs range from .05 to .37, depending on the subgroup/ specific methodology; Nguyen & Ryan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mathematics identification involves two components: feeling that you are good at mathematics and feeling that it is important to you to be good at mathematics (Smith & White, 2001). Research with high school and college students shows that women who are at least moderately identified with mathematics are more susceptible to stereotype threat effects than those who are not mathematics identified (Keller, 2007;Nguyen & Ryan, 2008;Smith & White, 2001).…”
Section: Conditions Under Which Stereotype Threat Effects Occurmentioning
confidence: 99%
“…Much research has been conducted investigating stereotype threat in samples of college women (see Nguyen & Ryan, 2008). Although researchers often consider stereotype threat to be a well-established phenomenon in college women, a recent review and meta-analysis calls the strength of this phenomenon into question, suggesting that claims that stereotype threat is a robust phenomenon are exaggerated (Stoet & Geary, 2012).…”
Section: Stereotype Threat Effects In Childhood and Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of studies (see, e.g., [55]) have found that individuals feel stress when placed in a situation where they run the risk of confirming a negative stereotype about their group (e.g., ethnicity). This stress can then cause poor performance [56,57].…”
Section: Why Is Creativity Important? the Issue Of Biasmentioning
confidence: 99%